2017
DOI: 10.1007/s00223-017-0259-2
|View full text |Cite
|
Sign up to set email alerts
|

Bone Alkaline Phosphatase and Tartrate-Resistant Acid Phosphatase: Potential Co-regulators of Bone Mineralization

Abstract: Phosphorylated osteopontin (OPN) inhibits hydroxyapatite crystal formation and growth, and bone alkaline phosphatase (BALP) promotes extracellular mineralization via the release of inorganic phosphate from the mineralization inhibitor inorganic pyrophosphate (PPi). Tartrate-resistant acid phosphatase (TRAP), produced by osteoclasts, osteoblasts, and osteocytes, exhibits potent phosphatase activity towards OPN; however, its potential capacity as a regulator of mineralization has not previously been addressed. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
56
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 51 publications
4
56
0
1
Order By: Relevance
“…Moreover, bone remodeling during AP is a defensive reaction to root canal infection, tending to an alveolar bone resorption due to an increase in osteoclastic activity. At the same time, ALP, which is important for mineral formation, tends to diminish due to decreased osteoblastic activity, contributing to the similarity of the results between the groups with and without apical lesions under alcohol administration.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, bone remodeling during AP is a defensive reaction to root canal infection, tending to an alveolar bone resorption due to an increase in osteoclastic activity. At the same time, ALP, which is important for mineral formation, tends to diminish due to decreased osteoblastic activity, contributing to the similarity of the results between the groups with and without apical lesions under alcohol administration.…”
Section: Discussionsupporting
confidence: 89%
“…It consistent with some reports, for example, cartilage is composed of specialized cells called chondrocytes that produce a large amount of collagenous extracellular matrix and are closer together creating less intercellular space . And TRAP produced by osteoclasts can alleviate the inhibitory effect of OPN on mineralization, suggesting a potential role for TRAP in skeletal mineralization . Furthermore, human calcitonin (hCt) is a small peptide hormone that exerts its physiological effect on Ca(2 + ) metabolism by means of osteoclast‐mediated bone resorption inhibition …”
Section: Discussionsupporting
confidence: 83%
“…The predominant role of BALP during mineralization is the inactivation of inhibitory polyphosphates 52 , most importantly the main autocrine calcification inhibitor PP i 53,54 . ALPs are also speculated to inactivate the calcification inhibitor osteopontin through dephosphorylation 55 and a 2017 study showed that human BALP can suppress the inhibitory effect of osteopontin on in vitro mineralization 56 . In addition, ALPs generate P i , which is the substrate of mineralization, by hydrolysation of organic phosphate esters 57 .…”
Section: Mechanisms Of Mineralizationmentioning
confidence: 99%